International Collaboration in Educational Management: Challenges and Opportunities in a Globalized World - Fauzan Ulwan Fadhlurrahman; Muhammad Diaz Wahyu Darmansyah; Yogi Permana Adi Citra (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This study explores the pivotal role of leadership and strategic vision in fostering successful international collaboration in educational management. Amid the complexities of cross-cultural partnerships, leaders with a global mindset, inclusivity, and flexibility are essential in aligning diverse stakeholders and navigating regulatory and cultural challenges. Through a comprehensive literature review of recent research, the study highlights how visionary leadership drives sustainable collaboration by promoting innovation, continuous learning, effective communication, capacity building, and ethical practices. The findings underscore that strong leadership not only facilitates operational coordination but also ensures the long-term development and resilience of international educational partnerships. These insights contribute to a deeper understanding of leadership dynamics necessary for enhancing global education management in an increasingly interconnected world.